Antimicrobial activities of Marcgraviaceae species and isolation of a naphthoquinone from Marcgravia nervosa (Marcgraviaceae) - Carballo Arce, Ana Francis (2015)
The Marcgraviaceae is a neotropical plant family of lianas and shrubs distributed throughout Central and South America, mainly in evergreen and semi-evergreen tropical forests. In this study, extracts of 12 Marcgraviaceae species were assessed for inhibition of bacterial quorum sensing (QS) in Chromobacterium violaceum, bacterial biofilm formation in Pseudomonas aeruginosa PA14, and fungal growth in Saccharomyces cerevisiae. Six species showed promising inhibitory activities in at least one of the three bioassays (Marcgravia nervosa Triana & Planch., Marcgravia polyantha Delp., Marcgravia schippii Standl., Marcgraviastrum subsessile (Benth.) Bedell, Schwartzia brasiliensis (Choisy) Bedell ex Gir-Cañas, and Schwartzia costaricensis (Gilg.) Bedell). Analyses of the crude extract of the leaves of Marcgravia nervosa using HPLC–APCI–MS showed the presence of five pentacyclic triterpenes: ursolic acid (2), betulinic acid (3), α–amyrin (4), β–amyrin (5), lupeol (6). Bioassay-guided fractionation of this plant resulted in the isolation and identification of 2-methoxy-1,4-naphthoquinone (1) as the active principle with a minimum inhibitory concentration (MIC) of 85–100 μmol·L−1 against Saccharomyces cerevisiae BY4741 (haploid) and BY4743 (diploid).